TATALAKSANA KOMUNIKASI PEMERIKSAAN KELAINAN REFRAKSI ANISOMETROPIA RENDAH ANAK SD USIA 6-8 TAHUN - Bunyamin Rizki Abdillah; Opep Cahya Nugraha2; M Wahyu Budiana3 (Jurnal Mata Optik, 2023)
In conducting a refractive examination of children the role of communication is very important, where we interact with patients, especially in children where our understanding and understanding communicate repeatedly. Eyestrain that often causes a feeling of laziness to read and study so that children's eyesight decreases. Therefore, the role of parents is very important in paying attention to their children when doing something, especially in vision which is a window to the world. Journal writing uses descriptive data collection with literature where smooth communication will get the right examination results.